EFEKTIFITAS BAHAN AJAR DAN MEDIA BERBASIS ICT PADA MATERI PERSAMAAN DAN FUNGSI KUADRAT - Rizki, Swaditya; Wildaniati, Yunita (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The objectives of this research are to know the practicality and the effectiveness of the development of teaching material and ICT-based media toward learning outcome on material of quadratic equations and function. Research subjects are mathematics education students of FKIP Muhammadiyah University of Metro. Experimental design uses a before-after or one group pretest-posttest technique. The technique of collecting data uses the questionnaires and tests. Data analysis uses paired sample t-test. The results obtained by the value of sig. = 0.000 where the value of Î± = 0.05 and the value of t = 6807> ttable = 2,015, so it can be concluded that the value of the pre-test and post-test was very significantly different. The marginal average was known that post-test value was greater than that of the pre-test, so it can be concluded that there was a significant effect of teaching materials and ICT-based media toward learning outcomes. In other words, the teaching materials and ICT-based media are very effective for teaching and learning.Keywords: teaching material and media, ICT, quadratic equations and function.